Comparative Study on Compaction and Sintering Behavior of Spray and Freeze Granulated Magnesium Aluminate Spinel Powder. Issue 2 (3rd April 2021) - Manivannan, Swathi; Biswas, Papiya; Barick, Prasenjit; Kumari, Sweety; Saha, Bhaskar Prasad; Johnson, Roy
Abstract : Commercially procured magnesium aluminate (MgAl2 O4 ) spinel powder with average particle size of 300 nm and irregular morphology were spray and freeze granulated. The granules were characterized for the texture, strength, granule size and its distribution. In order to evaluate the flowability of granules, rheological parameters, such as Carr index and Hausner ratio were measured. The granules were further subjected to quasi-static compaction under loading, unloading conditions and compaction curves were constructed. Compaction coefficients thus obtained were correlated with granulation conditions and other parameters including green densities. Compacted green samples were also subjected to flexural strength measurements following ASTM standards and fractographs were observed under FESEM. A Carr index of 13.7 and Hausner ratio of 1.16 were obtained for freeze dried granules indicating the superiority in flow behavior as compared to its spray granulated counterpart, thereby showing a better compaction behavior: compaction coefficient of 5.9 in combination with higher true and predicted green density values and lower granule strength of 1.22 MPa. The green samples exhibited a flexural strength of 11 and 12.5 MPa and compressive strength of 2.44 and 1.22 MPa for spray and freeze granulated sample, respectively. The above observations were also complemented by the fractographs. GRAPHICAL ABSTRACT: UF0001